(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
The paper is dedicated to review of possibilities of application of one of the most perspective approaches for new interesting molecular objects - nano-sized exchange clusters of high nuclearity - use of processes of hierarchical self-assembly in solution.